Open-Circuit Voltage Enhancement on the Basis of Polymer Gel Electrolyte for a Highly Stable Dye-Sensitized Solar Cell - Wu, Congcong; Jia, Lichao; Guo, Siyao; Han, Song; Chi, Bo; Pu, Jian; Jian, Li (American Chemical Society, 2013)
Dye-sensitized solar cells (DSSC) have received considerable attention owing to their low preparation cost and easy fabrication process. However, one of the drawbacks that limits the further application of DSSC is their poor stability, arising from the leakage and volatilization of the liquid organic solvent in the electrolyte. Therefore, to improve the long-term stability of DSSC, polymer gel electrolyte was studied to replace the conventional liquid electrolyte in this work. The results show that compared to liquid electrolyte, DSSC with polymer gel electrolyte has a smaller short-circuit current (Jsc), which decreases with the increase of the polymer gelator. Nevertheless, with the employment of the polymer gel electrolyte, there is a significant enhancement of open-circuit voltage (Voc), and it increases with the increase of the polymer gelator content. The highest Voc, up to 0.873 V, can be obtained for DSSC with a 30% polymer gelator content. The impact of the polymer gel electrolyte on the photovoltaic performance of DSSC, especially on Voc, was studied by analyzing the charge-transfer kinetics in the polymer gel electrolyte. Furthermore, the influence of the polymer gel electrolyte on the long-term stability of DSSC was also investigated.